Fatalism in the context of COVID-19: Perceiving coronavirus as a death sentence predicts reluctance to perform recommended preventive behaviors. (August 2020) - Jimenez, Tyler; Restar, Arjee; Helm, Peter J.; Cross, Rebekah Israel; Barath, Deanna; Arndt, Jamie
Abstract: To manage the spread of coronavirus, health entities have urged the public to take preventive measures such as social distancing and handwashing. Yet, many appear reluctant to take these measures. Research is needed to understand factors underlying such reluctance, with the aim of developing targeted health interventions. We identify associating coronavirus with death as one such factor. 590 participants completed surveys in mid-March 2020, which included attitudes toward coronavirus, preventive behavioral intentions, and sociodemographic factors. Associating coronavirus with death negatively predicted intentions to perform preventive behaviors. Further, associating coronavirus with death was not evenly distributed throughout the sample and was related with a number of sociodemographic factors including age, race, and availability of sick leave. Following recommended preventive measures to slow the spread of coronavirus appears to relate to the degree to which people associate coronavirus with death. These findings can be used by public health researchers and practitioners to identify those for whom targeted health communication and interventions would be most beneficial, as well as to frame health messaging in ways that combat fatalism. Highlights: Age, race, and ability to take sick leave predict associating coronavirus with death. Such associations are negatively correlated with preventive behaviors such as handwashing and social distancing. The findings inform resistance to preventive behaviors and point to the need for targeted health communication.